Impactos da sojicultura de exportação sobre a biodiversidade do Cerrado / Impacts of the international trade of soybeans on the biodiversity of Cerrado Savannah - Fábio Albergaria de Queiroz (Sociedade & Natureza)
The complex relationship between free trade and environment is, nowadays, one of the mostimportant issues found at the international affairs agenda. Much has been discussed, but fewconclusive answers on the so-called environmental impact by free trade have been drawn. Anaccurate analysis on the issue will depend on the individual study of each case due to its complexity.In order to verify such assumption this paper has analyzed the impacts of the international trade ofsoybeans on the biodiversity of Cerrado Savannah. From that specific study it has been possible toverify the existence of a direct relationship between the international trade of soybeans and theloss of biodiversity in that biome.